PENDAPATAN USAHATANI PADI YANG MENERAPKAN SISTEM RESI GUDANG DI KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Mutiara Indira Putri; R Hanung Ismono; Yaktiworo Indriani (Lampung University, 2017)
This study aims to analyze the income level and the efficiency of rice farming that joining the warehouse receipt system and non warehouse receipt system, and identify contributing factors and inhibiting factors to the implementation of warehouse receipt system for rice farmers. This research was conducted in Pulau Panggung Sub District of Tanggamus Regency which data was collected in April 2016. The sample was selected by census technique method for the farmers who are joining the warehouse receipt system and simple random sampling method for the farmers who are not joining the warehouse receipt system. The data was analyzed by farm income analysis and Decision Matrix Analysis (DMA). The results of this research showed that the income of farmers who were joining the warehouse receipt system was higher than farmers who were not joining the warehouse receipt system. The total income of farmers who were joining the warehouse receipt system was Rp5,148,487.78 in the first planting season and Rp7,120,807.78 in the second planting season, while the total income of farmers who were not joining the warehouse receipt system was Rp3,881,849.76 and 5,029,974.72 respectively. The farmer influencing factor on joining the warehouse receipt system was the cost was cheap, while influencing factor on unjoining the warehouse receipt system was the low socialization to farmers. Key words : farm income, rice, warehouse receipt system